TOURISM RESERVATION INFORMATION SYSTEM BASED ON THE PENTAGO CASE STUDY WEBSITE RIVERSIDE GARDEN - Dhea Aulia; Mukhroji Mukhroji; Rossiana Ginting; Satria Prayudi (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research is entitled Website-Based Tourist Attraction Reservation Information System by conducting a case study at Pentago Garden Riverside, located in Central Aceh, Bener Meriah. The aim of this research is to design and build a tourist reservation information system to make it easier for visitors to make reservations about the facilities available at Pentago Garden Riverside, as well as designing a conventional reservation system with a more modern approach. The research and development method using the waterfall method used is a descriptive approach by collecting data through observation, interviews and literature studies. This system design uses the UML (Unified Modeling Language) design model, and was developed using the PHP programming language and for storage using a MySQL database. The result of this research is a website-based tourist reservation information system that allows visitors to make online reservations easily. Users can access information about tourist attractions, make reservations by selecting facilities and determining the date of visit, and make payments online. Admin can manage visitor and transaction data, generate income reports. In conclusion, this website-based tourist attraction reservation information system provides convenience and comfort for visitors and managers of Pentago Garden Riverside. With this system, it is hoped that ordering and data processing will become smoother, provide a better experience for visitors, and support the development of tourist attraction businesses.